2014
DOI: 10.1136/annrheumdis-2014-205389
|View full text |Cite
|
Sign up to set email alerts
|

Association between tobacco smoking and response to tumour necrosis factor α inhibitor treatment in psoriatic arthritis: results from the DANBIO registry

Abstract: In PsA, smokers had worse baseline patient-reported outcomes, shorter treatment adherence and poorer response to TNFi's compared to non-smokers. This was most pronounced in men and in patients treated with infliximab or etanercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
6
46
0
3
Order By: Relevance
“…The most common reasons for discontinuation of TNFi treatment in PsA are lack of efficacy and, to a lesser extent, adverse events . Moreover, previous studies have identified other factors that seem to influence TNFi outcomes in PsA, including baseline C‐reactive protein (CRP) level, concomitant methotrexate treatment, sex, and body mass index (BMI) . However, few previous studies have investigated whether the number and severity of somatic and psychiatric comorbid diseases influence TNFi treatment response and persistence in patients with PsA .…”
Section: Introductionmentioning
confidence: 99%
“…The most common reasons for discontinuation of TNFi treatment in PsA are lack of efficacy and, to a lesser extent, adverse events . Moreover, previous studies have identified other factors that seem to influence TNFi outcomes in PsA, including baseline C‐reactive protein (CRP) level, concomitant methotrexate treatment, sex, and body mass index (BMI) . However, few previous studies have investigated whether the number and severity of somatic and psychiatric comorbid diseases influence TNFi treatment response and persistence in patients with PsA .…”
Section: Introductionmentioning
confidence: 99%
“…Smokers have also been shown to have a shorter treatment adherence and a poorer response to TNFi in psoriatic arthritis 5. The impact of tobacco use in patients with axial spondyloarthritis (axSpA) is only beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that smoking can increase the activity of spondyloarthritis and rheumatoid arthritis, thus reducing quality of life. [61][62][63] Hojgaard et al 64 conducted an observational research of 1388 psoriatic patients to study the correlation between smoking and treatment effect of TNF-a inhibitors. The result showed that heavy smoking could decrease the treatment effect of TNF-a-targeted drugs, and the impact seemed partially reversible.…”
Section: Smokingmentioning
confidence: 99%